The scourge of Asian Flu: In utero exposure to pandemic influenza and the development of a cohort of British children - Elaine Kelly (Institute for Fiscal Studies (IFS), 2009)
This paper examines the impact of in utero exposure to the Asian influenza pandemic of 1957 upon physical and cognitive development in childhood. Outcome data is provided by the National Child Development Study (NCDS), a panel study of a cohort of British children who were all potentially exposed in the womb. Epidemic effects are identified using geographic variation in a surrogate measure of the epidemic. Results indicate significant detrimental effects of the epidemic upon birth weight and height at 7 and 11, but only for the offspring of mother's with certain health characteristics. By contrast, the impact of the epidemic on childhood cognitive test scores is more general: test scores are reduced at the mean, and effects remain constant across maternal health and socioeconomic indicators. Taken together, our results point to multiple channels linking foetal health shocks to childhood outcomes.
Keywords: I12; I29; D13; 330; NCDS; Foetal Origins; Birth Weight; Influenza; Krankheit; Epidemie; Schwangerschaft; Kinder; Gesundheit; Großbritannien